Significant metal enhanced fluorescence of Ag2S quantum dots in the second near-infrared window - Theodorou,IG; Jawad,Z; Qin,H; Aboagye,EO; Porter,A; Ryan,M; Xie,F (Nanoscale, 2016)
The amplification of light in NIR-II from Ag2S QDs via metal enhanced fluorescence (MEF) is reported for the first time. Significant fluorescence enhancement of over 100 times for Ag2S QDs deposited on Au-nanostructured arrays, paves the way for novel sensing and imaging applications based on Ag2S QDs, with improved detection sensitivity and contrast enhancement.